Intravital imaging of immune responses in intestinal inflammation - Masaki Honda; Masashi Kadohisa; Daiki Yoshii; Yoshihiro Komohara; Taizo Hibi (BMC, 2023)
Abstract To date, many kinds of immune cells have been identified, but their precise roles in intestinal immunity remain unclear. Understanding the in vivo behavior of these immune cells and their function in gastrointestinal inflammation, including colitis, inflammatory bowel disease, ischemia-reperfusion injury, and neutrophil extracellular traps, is critical for gastrointestinal research to proceed to the next step. Additionally, understanding the immune responses involved in gastrointestinal tumors and tissue repair is becoming increasingly important for the elucidation of disease mechanisms that have been unknown. In recent years, the application of intravital microscopy in gastrointestinal research has provided novel insights into the mechanisms of intestine-specific events including innate and adaptive immunities. In this review, we focus on the emerging role of intravital imaging in gastrointestinal research and describe how to observe the intestines and immune cells using intravital microscopy. Additionally, we outline novel findings obtained by this new technique.